Waste materials as extender of bituminous binder: a review - Shahreena Melati Rhasbudin Shah,; Siti Norfatihah Awang,; Tey, Li-Sian; Yee, Hooi Min (Penerbit Universiti Kebangsaan Malaysia, 2023)
Bitumen is a hydrocarbon material which can be largely obtained from crude petroleum distillation. It used widely in flexible pavement construction as a binder that binds the aggregate. Flexible pavements make up around 95% of the pavement in entire world. The quality of the materials used in the flexible pavement is essential for its performance. The modification of bituminous binders using modifiers is applied to improve the quality and properties of bitumen. Due to the limitation of crude oil, higher price, and impact of bitumen on the environment, an efficient, cost-effective, and environmentally friendly modifier for the modification of bituminous binders is vital in road industry. This paper aims to provides a review and propose the waste materials that can be used as modifier or bitumen extender. Among these waste materials, silicon, rubber, cooking oil (mix with other modifiers) lignin and calcium lignosulfonate shown a promising results as bitumen extender. Furthermore, the cost analysis of the modified bituminous binders was also look upon. The findings from this study recommend lignin among the extender being compared. Lignin can be mixed directly in the bitumen with a minimal process involved. Moreover, lignin is a bio-based waste materials and the second most abundant organic material on earth, after cellulose. With 25% replacement of bitumen, lignin reduces the consumption of non-renewable bitumen and has a great potential to be used in pavement construction.